SHARIA COMPLIANCE OF PNM MEKAAR SYARIAH FINANCING UNDER DSN-MUI FATWA NO 141 - Abu, Risna Agusalim; Aisya, Sitti; Asmarini, Andini; Ruslan, Murniati (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study aims to examine the sharia compliance of financing practices at PNM Mekaar Syariah Unit Botugolu based on the provisions of the National Sharia Council–Indonesian Ulema Council (DSN-MUI) Fatwa No. 141/DSN-MUI/VIII/2021 concerning the Guidelines for the Establishment and Operation of Sharia Cooperatives. This research employs an empirical legal research design with a socio-legal approach, analyzing the relationship between Sharia legal norms (das sollen) and financing practices implemented in the field (das sein). Data were collected through observations, in-depth interviews with management and customers, and documentary analysis of contracts and institutional operational procedures. The findings indicate that PNM Mekaar Syariah plays a role in expanding access to capital for ultra-micro business actors. However, the study also identifies several practices that require adjustment to better align with the fatwa provisions, particularly concerning the strengthening of sharia supervisory functions, the implementation of Murabahah and Wakalah contracts, the determination of service charges, the mandatory savings mechanism, and the application of the joint liability system, which explicit guarantee contracts have not fully supported. This study concludes that strengthening sharia governance and refining the design of financing contracts are necessary to enhance the alignment of PNM Mekaar Syariah’s operations with the principles of justice, transparency, and public benefit in sharia economic law. Abstrak Penelitian ini bertujuan untuk mengkaji kepatuhan syariah praktik pembiayaan PNM Mekaar Syariah Unit Botugolu berdasarkan ketentuan Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) Nomor 141/DSN-MUI/VIII/2021 tentang Pedoman Pendirian dan Operasional Koperasi Syariah. Penelitian ini merupakan penelitian hukum empiris dengan pendekatan socio-legal, yang menelaah hubungan antara norma hukum syariah (das sollen) dan praktik pembiayaan yang berlangsung di lapangan (das sein). Data diperoleh melalui observasi, wawancara mendalam dengan pengelola dan nasabah, serta studi dokumentasi terhadap akad dan prosedur operasional lembaga. Hasil penelitian menunjukkan bahwa PNM Mekaar Syariah memiliki peran dalam memperluas akses permodalan bagi pelaku usaha ultra mikro. Namun demikian, penelitian ini menemukan beberapa praktik yang memerlukan penyesuaian agar selaras dengan ketentuan fatwa, antara lain terkait dengan penguatan fungsi pengawasan syariah, penerapan akad Murabahah dan Wakalah, penetapan imbal jasa, mekanisme simpanan wajib, serta penerapan sistem tanggung renteng yang belum sepenuhnya didukung oleh akad penjaminan yang eksplisit. Penelitian ini menyimpulkan bahwa penguatan tata kelola syariah dan penyempurnaan desain akad pembiayaan diperlukan guna meningkatkan keselarasan operasional PNM Mekaar Syariah dengan prinsip keadilan, transparansi, dan kemaslahatan dalam hukum ekonomi syariah.